2023
DOI: 10.3390/life13061406
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinoma Perineural Invasion and Suggestive Signs of Perineural Invasion—Findings and Perspectives

Elena Niculet,
Carmen Bobeica,
Cristian Onisor
et al.

Abstract: Basal cell carcinoma (BCC) is a malignant tumor with a rising incidence and is the beneficiary of several innovative evaluation techniques. Histopathology remains the gold standard for assessment, having the possibility of addressing multiple high-risk factors such as perineural invasion (PNI). The current study included a number of 244 BCC patients and targeted the identification of positive PNI and its suggestive signs, and whether they correlated or not with other high-risk tumor signs. PNI was found in 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…However, it is important to note that one of the patients’ lesions was located on the nasal area. The nose is a favored site for perineural invasion (PNI) in BCC [ 37 , 38 ]. Perineural invasion in BCC is an important pathological finding in which tumor cells invade the spaces surrounding nerves.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that one of the patients’ lesions was located on the nasal area. The nose is a favored site for perineural invasion (PNI) in BCC [ 37 , 38 ]. Perineural invasion in BCC is an important pathological finding in which tumor cells invade the spaces surrounding nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that cSCC can perineurally invade the surrounding soft tissues ( 115 , 116 ); this finding suggests that in contrast to, for example, melanoma, the processes of cancer spread depend less on the lymphatic system and have multiple patterns of invasion ( 117 ). Often, during surgery for cSCC, a tumor that travels via a cranial nerve to the base of the skull is identified ( 118 ), which may be treated via radiotherapy ( 119 ). On pretreatment radiographs, a tumor that has spread to the brain via the cranial foramen may often be visible; nevertheless, it is important to highlight that individuals with such tumors are unlikely to be cured and that such tumors are no longer amenable to surgery ( 120 ).…”
Section: Discussionmentioning
confidence: 99%